Dialektika Social Entrepreneurship dan Fiqih Sosial - Fittria, Anis (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2019)
This paper aims to find out dialectics social entrepreneurship and social fiqh. Social entrepreneurship is a concept that combines social empowerment and entrepreneurship. Social Fiqh is fiqh that able to dialogue with development era. This study include in field research that uses qualitative research methods. The results of this study indicate that social entrepreneurship is in accordance with the concept of fiqh social that has five things (al-dharuriyyat al-khamsah). First, social entrepreneurship according to hifdz al-din (religion maintain). Second, hifdz al-aql (mind maintain). Third, hifdz al-nafs (soul maintain). Fourth, hifdz al-mal (wealth maintain). Fifth, hifdz al-nasl (generation maintain), also hifdz al-bi’ah (environtment maintain)